2019
DOI: 10.1093/infdis/jiz455
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Induction in Nipah Virus–Infected Primary Human and Porcine Bronchial Epithelial Cells

Abstract: During the Nipah virus (NiV) outbreak in Malaysia, pigs and humans were infected. While pigs generally developed severe respiratory disease due to effective virus replication and associated inflammation processes in porcine airways, respiratory symptoms in humans were rare and less severe. To elucidate the reasons for the species-specific differences in NiV airway infections, we compared the cytokine responses as a first reaction to NiV in primary porcine and human bronchial epithelial cells (PBEpC and HBEpC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…As the human airway cell line A549 is known to respond to viral infection with the upregulation of type I (IFN-α/β) and type III IFN (IFN-λ) [ 54 ], we quantified the IFN-β and IFN-λ expression. As shown in Figure 5 B, both IFNs were clearly induced, with IFN-λ being more efficiently upregulated, consistent with our earlier observations in human primary airway epithelial cell cultures [ 51 , 55 ]. IFN induction in NiV-infected cell cultures also led to the upregulation of several ISGs, as exemplified by PKR, OAS, ISG56 and MxA ( Figure 5 C).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As the human airway cell line A549 is known to respond to viral infection with the upregulation of type I (IFN-α/β) and type III IFN (IFN-λ) [ 54 ], we quantified the IFN-β and IFN-λ expression. As shown in Figure 5 B, both IFNs were clearly induced, with IFN-λ being more efficiently upregulated, consistent with our earlier observations in human primary airway epithelial cell cultures [ 51 , 55 ]. IFN induction in NiV-infected cell cultures also led to the upregulation of several ISGs, as exemplified by PKR, OAS, ISG56 and MxA ( Figure 5 C).…”
Section: Resultssupporting
confidence: 91%
“…Quantitative PCR (qPCR) analysis was performed as described previously [ 50 , 51 ]. Total RNA was isolated from lysates of infected cells (RNeasy Kit, Qiagen, Venlo, Netherlands) and reverse-transcribed with oligo(dT) 18 primers (RevertAid First Strand cDNA Synthesis Kit, ThermoFisher).…”
Section: Methodsmentioning
confidence: 99%
“…HAE retain the functional IFN signaling cascades that robustly induce type I and III IFNs in vivo in response to viral infections and have been used to model innate immune responses to viral infections, including respiratory syncytial virus (RSV), pneumovirus ( 38 , 39 ), influenza A virus ( 40 ), and SARS-CoV-2 ( 41 ), as well as other Paramyxoviridae family members such as Nipah virus ( 42 ) and parainfluenza viruses ( 43 ). Of note, RSV-infected HAE show increased antiviral cytokine and chemokine expression despite minimal induction of type I IFNs ( 38 , 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Nipah virus (NiV) infects the respiratory tract of both humans and pigs. However, while NiV-infected pigs develop an acute and often severe inflammatory-mediated respiratory disease, symptoms are seen only in few NiV-infected human patients ( 13 ). Comparative studies using primary cultures of human and porcine bronchial epithelial cells infected with NiV revealed that both RECs responded to NiV infection by producing IFN-λ and antiviral factors ( OAS and ISG-56 ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies using primary cultures of human and porcine bronchial epithelial cells infected with NiV revealed that both RECs responded to NiV infection by producing IFN-λ and antiviral factors ( OAS and ISG-56 ). Human cells were more efficient than porcine cells to up-regulate IFN-λ and antiviral factors, which correlated with lower viral RNA content ( 13 ). Of note, while porcine bronchial epithelial cells had a reduced capacity to produce IFN-λ, they were capable to strongly express the proinflammatory cytokines IL-6 and IL-8 , which were suggested to contribute to inflammatory-pathology.…”
Section: Introductionmentioning
confidence: 99%